Society for Academic Emergency Medicine Statement on Plagiarism. (18th September 2017) - Asher, Shellie L.; Iserson, Kenneth V.; Merck, Lisa H.
Abstract: The integrity of the research enterprise is of the utmost importance for the advancement of safe and effective medical practice for patients and for maintaining the public trust in health care. Academic societies and editors of journals are key participants in guarding scientific integrity. Avoiding and preventing plagiarism helps to preserve the scientific integrity of professional presentations and publications. The Society for Academic Emergency Medicine (SAEM) Ethics Committee discusses current issues in scientific publishing integrity and provides a guideline to avoid plagiarism in SAEM presentations and publications.